Incidencia del nivel de educación de los padres y madres de familia en el rendimiento escolar en los niños y niñas de la escuela de educación básica 5 de Abril del sitio San Vicente del cantón El Guabo, provincia de El Oro, periodo escolar 2012-2013. - Villacrés Pauta, Pamela Vanessa (2016)
The bulk of studies on academic performance are limited in the projective plane, as feasible educational problems to be understood only through their empirical representations. These are expressed, usually results in a given school process, which tends to recognize and systematize the yield from representations such as student grades among others. The present research work “IMPACT OF EDUCATION LEVEL OF PARENTS OF FAMILY IN SCHOOL PERFORMANCE IN CHILDREN SCHOOL OF BASIC EDUCATION “5 DE ABRIL” SITE SAN VICENTE, DEL CANTÓN EL GUABO, PROVINCIA DE EL ORO, 2012 – 2013, has considerable importance because of the importance in education. The results obtained from this work will provide a useful source of information to propose alternatives that can improve the problem of academic performance as a result of the impact of the educational level of parents in the education of their children.